Prospecção e avaliação de viabilidade de três ligas de aço inoxidável para aplicação em componentes de sistemas hidrelétricos - Furlan, Felipe Rosa (Universidade Federal de São Carlos, 2025)
The hydroelectric sector stands as the main source of energy generation in Brazil, accounting for approximately 60% of the installed capacity. However, many plants have been operating for decades, accumulating wear-related damage and increasing maintenance costs—one of the sector's main challenges. In this context, this study evaluates the feasibility of replacing martensitic stainless steel AISI 420 with austenitic alloys AISI 201LN and AISI 304 in components of hydroelectric systems subjected to wear. Microstructural characterization, Brinell hardness testing, micro-adhesive wear tests (ball crater), and scanning electron microscopy (SEM) analyses of the worn surfaces were conducted. All alloys exhibited hardness values above 200 HB, meeting the minimum requirement for applications involving self-lubricating composite materials. The results showed that the austenitic steels, particularly AISI 201LN, presented lower wear rates compared to AISI 420, despite similar hardness levels. This improved performance is attributed to greater work hardening capability and strain-induced phase transformation, associated with low stacking fault energy (SFE). The analysis of Carbon Equivalent (CE) also revealed an inverse correlation with wear rate. Despite the promising results, further testing under real operating conditions, especially involving contact with self-lubricating composites, is recommended. The study concludes that material substitution is technically feasible, with potential benefits in cost reduction and increased durability.
Prospection and feasibility assessment of three stainless steel alloys for application in hydropower system components
Keywords: Aços inoxidáveis; Energia hidrelétrica; Resistência ao desgaste; Dureza; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA